Разложите ** множители 9-(2c-1)^2.

0 голосов
24 просмотров

Разложите на множители 9-(2c-1)^2.


Алгебра | 24 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

9 - (2с - 1)² = 3² - (2с - 1)² = (3 - 2с + 1)(3 + 2с - 1) = (4 - 2с)(2 + 2с) = 4(2 - с)(1 + с)

(13.3k баллов)
0

просто привели подобные

0

первая скобка: 3 - 2c + 1 = (3 + 1) - 2c = 4 - 2c

0

вторая скобка: 3 + 2c - 1 = (3 - 1) + 2c = 2 + 2c

0

из первой скобки вынесли 2: 4 - 2c = 2(2 - c)

0

из второй скобки вынесли 2: 2 + 2c = 2(1 + c)

0

и получилось 2 * (2 - с) * 2 * (1 + с) = 4(2 - с)(1 + с)

0

пожалуйста)

0 голосов

= (3 - (2с-1))(3 + (2с-1)) = (2 - 2с)(2 + 2с)

(10.1k баллов)
0

3 - (2с - 1) = 3 - 2с + 1 = 4 - 2с